KERAGAAN USAHA TANI UBI CILEMBU DALAM RANGKA MENGKOPERASIKAN PETANI - Sudewa, Jaka (Coopetition : Jurnal Ilmiah Manajemen, 2019)
The agribusiness system of Cilembu farming consist of procurement of production facilities subsystem, on farm subsystem, marketing subsystem, subsystem of post harvest and subsystem of support. In this agribusiness system there are problem such as in procurement of production facilities subsystem is limited business capital to purchase production facilities so that the input production such as fertilizer are not always available every season only can be purchased if the previous harvesting business capital has been paid or if they get loans from middleman as well as marketing channels are still long and not favorable to the farmers and the selling price of â€œubi Cilembuâ€ is still determined by the middleman therefore the role of union is needed to overcome these problems. So in this case the cooperative can play a role in the cultivation of land that unites the lands of farmers who had small fragmented into one in order to have a large area so that it can produce higher production. If in terms of the scale of production to the results, the sum of all coefficients each shows less than one result, so that the scale of Cilembu cassava production is included inelastis, this role of the cooperative is needed in an effort to increase the production of production in the presence of cooperatives, the cooperative can provide guidance or intensive counseling to the members for cultivation of Cilembu yam cultivation can be increased production results. All respondent â€œubi Cilembuâ€ farmers agree with the idea of establishing an union.